A prática profissional do curso de medicina da UFSCar e as atividades de preceptoria: uma narrativa reflexiva - Saggin, Julia (Universidade Federal de São Carlos, 2023)
The main educational method used in medical courses in Brazil is based on the Flexner Report which proposed a reconstruction of the medical training model with emphasis on the biomedical model. Recently, the reformulation of aspects of medical training in Brazil for a curriculum that includes different areas of knowledge and not just biological content has been discussed. Considering this, active learning methodologies advanced and, in line with the principles of the public health system and the national curriculum guidelines, in 2006 the medicine course of the Federal University of São Carlos (UFSCar) was founded. The purpose of this study is to execute a reflective narrative about the six years passed in UFSCar medicine with a focus on the medical practice and preceptorship activities.
The professional practice of the UFSCar medical course and preceptorship activities: a reflective narrative
Keywords: Prática Médica; Medical course; Curso de medicina; Medical practice; Preceptoria; Preceptorship; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL